Prohibition of Violations of Heavy Human Rights - Ni Ketut Sari Adnyani (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the clause on protecting human rights Article 2 of the UDHR and the state responsibility for the types of genocide crimes of Article 6 of the Rome Statute as a response to the fanaticism of religion, culture, freedom, anarchy, radicalism, and underestimating pluralism, which tends to discriminate, witness and allowing people to kill, kill, and rape large numbers of nations. Type of normative legal research. The research approach used is a statutory approach and a case study approach. The results show that human rights violations by borrowing the concept of performative self-contradiction from the theory of criminology, legal protection, and state responsibility provide protection for citizens who assert their rights are severely limited by Article 2 of the UDHR's human rights protection clause and responsibility Article 25 states against the protection of human rights. Further understanding and unifying the various legal cases that Article 6 has produced so far: both target political human rights violations, attack liberal democracy in general; and the abuse of exclusive human rights, attacking the rights of others. Category of genocide or not, we need to pay attention to 2 (two) things, namely Actus Reus (action) and Mens Rea (evil intention) in action.